Improving E-Commerce Effectiveness Using Augmented Reality - Melati Rosanensi (Universitas Bumigora, 2020)
The research aims to increase the effectiveness of e-commerce using augmented reality so that it can be used for online sellers as an option for existing sales media. The target of the application of augmented reality kitchen tools such as plates, cups, bowls, and teapots which are small equipment are social media users (Instagram) such as housewives or career women who usually use smartphones. The approach taken to determine the e-commerce sales model by applying augmented reality technology is to refer to the results of the system tests conducted previously. The conversion process is carried out in the implementation of augmented reality-based e-commerce sales media by using the parallel conversion method, namely by implementing a new system alongside the old system. In this study using the reliability test method, normality test, and Wilcoxon different test paired samples. From the test results show that the data are in the area of â€‹â€‹rejection of Ho then accept Hâ‚ which means that changes occur before and after using augmented reality, with the conclusion that an increase in the effectiveness of e-commerce using augmented reality, for this augmented reality application can be used on e-sales media commerce instagram to enhance technological progress. The approach taken to find out the e-commerce sales model by applying augmented reality technology is to refer to the results of the system tests carried out previously. From the results of the questionnaire shows that there is an increase in effectiveness before and after using augmented reality, for this augmented reality application can be used on media e-commerce sales Instagram to improve technological progress. The conversion process carried out in the implementation of media sales of e-commerce based on augmented reality using the parallel conversion method, namely by applying a new system side by side with the old system. The process of selling e-commerce on Instagram using augmented reality and without augmenetd reality will still be done as a standard process in the kitchenzone sales process. The test results in this study used three methods, namely reliability testing with the results of data that is not realistic, normality test with abnormal data results, and different tests of Wilcoxon samples paired with the results of data in the Ho rejection area then accept Hâ‚ which means changes before and after using augmented reality, with the conclusion that there is an increase in the effectiveness of e-commerce using augmented reality.